Transition to adulthood of care leavers in Portugal and Spain - Díaz-Esterri, Jorge; Coelho, Carina; Sevillano-Monje, Verónica; Delgado, Paulo; De-Juanas, Ángel (Children and youth services review, 2025)
The lack of economic and employment opportunities for young people and the difficulty in defining the competences and skills needed to move towards the adult role are factors that hinder the achievement of autonomy and well-being for todaýs youth. This especially affects those young people whose life trajectories place them in vulnerable situations, as is the case of young people who left residential care. For them, who lack voice to self-advocate, reaching the age of majority means the cessation of guardianship, so that the entry into adulthood is of great significance and implies the beginning of a forced and accelerated process of independence. For this reason, in recent decades, in Spain and Portugal, structures have gradually been implemented to support young people leaving residential care in this difficult phase of their lives. The aim of this study was to explore the transition to adulthood of young people leaving residential care in Spain and Portugal. A mixed method was carried out, using online questionnaires and semi-structured interviews. The questionnaire was administered to a sample of 194 professionals and the interviews involved 21 professionals of both countries. The results of this cross-national study show insufficient resources to support emancipation and to meet the carer leavers need’s. Likewise, the difficulties inherent to the labour market and the growth in the price of housing, especially in large cities, are making it difficult to achieve the milestone of independent living. So, data collected allows us to conclude that it is necessary to anticipate, make more progressive and coordinated the transition between the protection system and independent living.